PERAN ZAKAT DALAM ISLAM - Ardianis Ardianis (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
One of the managers of zakat in the area of Government is BAZ (Badan Amil Zakat). The role of this institution provides the latest system in zakat management. this institution, must be immediately channeled to the mustahik according to the priority scale that has been compiled in the work program. The purpose of zalcat management is the increasing awareness of the community in the fulfillment and in the service of zakat worship, the increasing function and role of religious institutions in the effort to realize the welfare of society and social justice, as well as increasing the utilization and utilization of zakat.